Knowledge, attitude and practices of Ghanaian midwives regarding the use of ophthalmic medications among pregnant women - Samuel Kyei; Franklin Lartey Otoo; Emmanuel Kwasi Abu; Anastasia Adomah Ofori (Elsevier, 2018)
Background: Midwives are the primary healthcare attendants of pregnant women and have per their mandate among others to detect and manage minor ailments presented by pregnant women including ocular disorders. This study was, therefore aimed at assessing the knowledge, attitude, and practices (KAP) of Midwives regarding the use of topical ophthalmic medications in managing common ocular diseases in pregnancy. Methods: Simple proportionate sampling was used to recruit midwives across the ten regions of Ghana. Participants completed a semi-structured questionnaire. KAP scores were computed as frequencies and percentages. Data were analyzed using Cross tabulations and Spearman's non-parametric correlation to determine associations. Results: A total of 273 registered midwives aged between 20 and 68 years participated in the study. The results indicated that 56.8% of midwives had low knowledge on ophthalmic medication use and 60.4% scored below average on their practice regarding ophthalmic medication use among pregnant women. This reflected the "dispassionate attitude" (78.6%) of the midwives towards the use of ophthalmic medications. Red eyes (58.2%) were the most reported ocular symptom with bacterial conjunctivitis being the most (55.7%) diagnosed ocular disease by the participants. Most referrals made by the midwives were to ophthalmologists (59.9%) and ophthalmic nurses (38.8%). Conclusion: The study revealed that midwives had low knowledge on ophthalmic medications and for that matter their practice of ophthalmic medication use in pregnancy was unsatisfactory. This had influenced their laissez-faire attitude towards the administration of ophthalmic medications despite they receiving complaints of ocular symptoms and subsequent diagnosis. Keywords: Pregnancy, Knowledge, Attitude, Practice, Midwives, Trimester